The intellectual property dimension of bilateral and regional trade agreements in ASIA: implications for trade and development policy - Abdul Ghani Azmi, Ida Madieha (World Intellectual Property Organization, 2017)
Beginning with the twenty first century, there has been a flurry of free trade agreements, either in the form of bilateral or regional agreements or economic partnership agreements, which have been entered into between Asian countries. Many reasons have been afforded to this rise in bilateralism and regionalism, ranging from the need to foster closer international economic partnership to regulatory cooperation. A more market-driven reason would be the need to maintain a regional supply chain, which becomes more crucial after the Asian Financial Crisis. The non-conclusion of the WTO Doha Round negotiations, with the promise of a development agenda, has forced countries to resort to bilateralism. Eventually, there are always political and diplomatic motivations, i.e. countries would not want to lose out in the rat race for lower tariffs and opening of markets, especially for an export-oriented market economy like Malaysia. As most of these instruments contain binding obligations on intellectual property rights (IPRs), this article examines the provisions on IPRs in these Free Trade Agreements (FTAs), Bilateral Trade Agreements (BTAs) and Regional Trade Agreements (RTAs) (in particular, the Trans-Pacific Agreement) in the form of mandatory international accession and TRIPSPlus binding commitments. The paper ends with some prognosis on the implications of the web of FTA obligations on domestic policies of WTO members.